Penggunaan Teknik Shaping dengan Training pada Anak Autis - Rachmawaty, Fitria (Fakultas Psikologi Universitas Islam Negeri Maulana Malik Ibrahim, 2015)
Autism is a mental disorder in children were much discussed recently. The development of autism also increased sharply in recent decades. Autism was firSt introduced in a paper in 1943 by an American psychiatrist named Leo Kanner. He found eleven children who have the same characteristics, that is not able to communicate and interact with other individuals and very indifferent to the environment outside of himself, and his behavior seemed like living in his own world. In this case use the method assessment techniques with observation and interviews, and supported by several psychological teSts. Prominent features of autistic behavior itself is the difficulty in social interaction, communication language Stereotyped or repetitive. Besides, the client Still has not been able to express his desire, one of which is a small kekamar independently, for it will be used in this case shaping techniques in shaping the behavior of the new subjects in order to be better able to express his desire to go back to the room is small. Of the technique performed showed significant on the subject, namely the change of interesting hands accompanying teachers when they want to pee, to be able to say the word